When Does Stand-Alone Software Qualify as a Medical Device in the European Union?—The Cjeu's Decision in Snitem and What it Implies for the Next Generation of Medical Devices. (30th June 2020) - Minssen, Timo; Mimler, Marc; Mak, Vivian
Abstract: This contribution analyses the first decision by the Court of Justice of the European Union (CJEU) on the qualification and regulation of stand-alone software as medical devices. Referring to the facts of the case and the applicable European Union (EU) regulatory framework, the Court specifically found that prescription support software may constitute a medical device. This would even be the case where the software does not act directly in or on the human body. Yet, according to the CJEU, it is necessary that the intended purpose falls within one or more of the 'medical purpose' categories of the regulatory definition of 'medical device'. The case has important implications, not only for specific legal debates, but it also signifies a paradigm shift with a rapidly increasing digitalisation of the health and life sciences. This highlights the demand for continuous debates over the necessary evolution of the regulatory framework applying to the interface of medical artificial intelligence (AI) and Big Data.